DGKZ Acts as a Potential Oncogene in Osteosarcoma Proliferation Through Its Possible Interaction With ERK1/2 and MYC Pathway - Yu, Wenxi; Tang, Lina; Lin, Feng; Yao, Yang; Shen, Zan (Frontiers in Oncology, 2019)
Osteosarcoma (OS) is one of the most common primary bone tumors in children and young adults. The majority of osteosarcoma patients have limited alternative therapeutic options and metastatic patients generally have a poor prognosis. Thus, it is important to explore novel effective therapeutic targets in the treatment of osteosarcoma. Diacylglycerol kinase zeta (DGKZ) is a recently identified gene potentially associated with certain human carcinogenesis. However, the role of DGKZ in proliferation of osteosarcoma is still unclear. In this study, DGKZ's expression was firstly investigated in OS tumor samples and correlated with poor outcome in OS patients. Silence of DGKZ by shRNA hampered osteosarcoma cell growth and promoted cell apoptosis in vitro. In vivo, DGKZ's knockout also suppressed xenograft tumor proliferation as determined by bioluminescence imaging and weight/volume measurements. Meanwhile, Affymetrix GeneChip and Ingenuity Pathway Analysis (IPA) revealed that DGKZ knockdown resulted in a decreased activity of MYC pathway, and several target genes expression in MYC pathway were altered, including CCND1, CDKN2B, CDK6, PCNA, and EGR1. Furthermore, immunoprecipitation coupled with mass spectrometry (IP-MS) analysis was used to identify proteins that interacted with DGKZ in OS cells and revealed ERK1/2, a key MYC-interactor, to associate with DGKZ. Together, our study demonstrated that DGKZ might act as an oncogene in osteosarcoma via its possible interaction with ERK1/2 and MYC pathway.